Оцінка стану вугільної промисловості на тимчасово окупованих територіях Донбасу - Makarov V.M.; Perov M.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2018)
The war with Russia in the Ukrainian Donbas has significantly worsened the situation in domestic coal industry. In the occupied areas of Donbas, the coal industry in fact turned out in a catastrophic state, and the mines that are in state ownership suffered the most.With regard for the rather high degree of uncertainty about the future of occupied territories of the Donbas, it should be recognized that this uncertainty is to some extent extrapolated to the prospects of development of the entire coal industry in Ukraine. Therefore, the purpose of this article is to analyze the current state of coal mining enterprises in the temporarily occupied territories of Donbas and to determine the potential of coal mining in Ukraine at the return of occupied territories under the control of Ukrainian authorities.We analyze the state and prospects of development of mining enterprises of the coal industry, which are currently in the temporarily occupied territories of Donbas. The potential of coal mining in Ukraine up to 2040 at the return of occupied territories under the control of Ukrainian authorities is determined.Total volumes of coal production will reach 100 million tons, including 25 million tons in the territory that is currently occupied. As compared with the preliminary forecasts of development of the coal industry for the period up to 2040, the additional losses of mining potential of the coal industry as a result of the occupation of a part of the Donbas areas are estimated as 15–20 million tons.